A novel method to continuously map the surface integrity and cutting mechanism transition in various cutting conditions. (April 2020) - Xu, Dongdong; Liao, Zhirong; Axinte, Dragos; Hardy, Mark
Abstract: This research proposes an innovative method to study the machined surface integrity and the variation of cutting mechanisms during a continuous rapid transition between different cutting conditions with an example for a nickel-based superalloy as workpiece material. For the first time, a machined surface covering a wide range of cutting speeds in a single cutting test has been generated, able to capture a clear variation (from serrated to continuous) of chip morphologies and provide a way for in-depth understanding of cutting phenomena. Different material characterisation techniques, including Scanning Electron Microscope (SEM), Electron Back-Scattered Diffraction (EBSD), and X-ray diffraction (XRD), were used to quantitatively evaluate the plastic deformation of the machined surface captured at various cutting speed in a single test. The results show a high potential for the application of this method to continuously study the cutting mechanism transition between different cutting conditions and rapidly characterise the machining behaviour of advanced materials, from the point of views of surface integrity and portioning of cutting energy. Graphical abstract: Image 1 Highlights: Proposed an innovative method to continuously capture the chip formation in different cutting conditions. Successfully captured the variation of cutting mechanisms during a continuous rapid transition in single test. Build a method to continuously evaluate the superficial surface integrity from the point of cutting energy.